2010
DOI: 10.1007/s00445-010-0363-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the early stages of catastrophic stratovolcano flank-collapse using analogue models

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Based on their field observations, Clavero et al (2002) suggested that glaciation of the western flank of Old Cone may have weakened the edifice, contributing to the collapse, and downslope movement and spreading of the debris avalanche were likely accommodated by shearing of the basal layer and disintegration of the edifice along preexisting fracture planes in the volcanic rocks. This model of emplacement is generally supported by physical modeling experiments of Andrade and van Wyk de Vries (2010). The morphological observations of all previous studies are consistent and conclude that the sector collapse and debris avalanche formed in a single event.…”
Section: Debris Avalanchesupporting
confidence: 84%
“…Based on their field observations, Clavero et al (2002) suggested that glaciation of the western flank of Old Cone may have weakened the edifice, contributing to the collapse, and downslope movement and spreading of the debris avalanche were likely accommodated by shearing of the basal layer and disintegration of the edifice along preexisting fracture planes in the volcanic rocks. This model of emplacement is generally supported by physical modeling experiments of Andrade and van Wyk de Vries (2010). The morphological observations of all previous studies are consistent and conclude that the sector collapse and debris avalanche formed in a single event.…”
Section: Debris Avalanchesupporting
confidence: 84%
“…From the perspective of volcanic geology, many studies have investigated the internal sedimentological features of deposits in the context of rockslide-debris avalanche transport mechanisms (Nakamura, 1978;Mimura et al, 1982;Watanabe, 1984;Ui et al, 1986;Glicken, 1996;Takarada et al, 1999;Clavero et al, 2002;Bernard et al, 2008;. Analog modeling also has been used to explore the kinematics of avalanches van Wyk de Vries, 2008, 2010;Andrade and van Wyk de Vries, 2010). The most recent studies such as those refined to provide dynamic scenarios of rockslide-debris avalanche emplacement based on detailed structural analysis of natural avalanches.…”
Section: Introductionmentioning
confidence: 98%
“…The extensional regime can produce normal and reverse faults, thus generating a series of ridges and grabens near the avalanche source Andrade and van Wyk de Vries, 2010;Paguican et al, 2012a). The transitions between these stress regimes probably cause the local changes of average displacement angle along the avalanche flow path.…”
Section: Topographical Constraints On Hummock Alignment Caused By Strmentioning
confidence: 97%
“…Analogue modeling of debris avalanche movements Andrade and van Wyk de Vries, 2010;Paguican et al, 2012a) has shown that during sliding, extensional conditions prevail within the proximal part of the avalanche and compressional conditions within the distal part, and that there may be alternating compressional and extensional regimes in the intermediate part of the flow. The extensional regime can produce normal and reverse faults, thus generating a series of ridges and grabens near the avalanche source Andrade and van Wyk de Vries, 2010;Paguican et al, 2012a).…”
Section: Topographical Constraints On Hummock Alignment Caused By Strmentioning
confidence: 98%